China’s Regional Policy and the Influence of the EU Assistance - Kamiński, Tomasz (European Spatial Research and Policy, 2009)
The EU has an interest in determining the form of internal reforms in China, as well as a lot of experience and know-how to share. Due to this fact it tries to support the process of Chinese transformation, in the form of various sectoral dialogues with China as well as by implementation of many projects financed by the EU. The aim of this paper is to analyse the EU policy towards China in the context of Chinese regional policy that struggles with growing inequalities between provinces. It examines the EU assistance programmes for China as well as sectoral dialogue concerning regional policy to answer the question whether the EU regional policy, with its 20 years of experience, could possibly be the pattern form China. Firstly, a short outlook has been given on regional inequalities in China. Secondly, the EU assistance programmes and sectoral dialogue have been analysed. Finally, the major research problem - what are the limitations of the EU’s assistance influence on China - has been investigated.